Legal Consequences of Prounouncing Sighat Taklik Talak Based on Decree of The Minister of Religion of The Republic of Indonesia Number 75 of 2014 - Na’imulloh, Marsyudi (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Sighat taklik talak contained in the excerpt of the marriage certificate has been applied in the Regulation of the Minister of Religion Number 2 of 1990, that in the sighat taklik talak is felt to occur easily, because of the parameter of taklik talak in the sighat is not specific. therefore things that are not considered potential reasons for divorce can come out as a result of the fall of divorce or even vice versa that things that are considered to be potential reasons for the fall of divorce can settle into non-results the fall of divorce. This research uses a qualitative approach, research that is included in field research. The implementation of sighat taklik talak is carried out in two ways, namely The reading and understanding of taklik talak is done in front of the registrar of marriage and not in front of the registrar of marriage. However, the signing as proof of reading the sighat taklik talak is carried out before the registrar of the marriage leaves the contract venue. When the above matters are violated by the husband, while the wife is not pleased and is reported by the wife, then taklik talak falls with talak khul'i.